Can specific treatment prevent progressive tendon degeneration?. Issue 4 (27th March 2011) - Alfredson, H
Abstract : Background: Tendon degeneration is generally believed to be irreversible. Objective: To use ultrasound to study the Achilles midportion tendon structure and thickness before and after treatment of chronic painful tendinosis. Design: Prospective study. Patients and interventions: Middle aged patients on varying activity levels, having midportion chronic Achilles tendinosis, were followed with ultrasound examinations before and after treatment with eccentric training, sclerosing polidocanol injections and surgical scraping. Outcome measurements: Tendon thickness and structure. Results: 89 patients successfully treated (pain-free during tendon loading) with eccentric training (n=22), sclerosing polidocanol injections (n=38) and surgical scraping (n=29), had a significantly thinner Achilles midportion and a more normal tendon structure, after compared to before, treatment. Conclusion: For the Achilles midportion, tendon degeneration might not be irreversible. The findings indicate a possible regeneration potential.